2022
DOI: 10.3390/ijms232415650
|View full text |Cite
|
Sign up to set email alerts
|

3-Bromopyruvate Suppresses the Malignant Phenotype of Vemurafenib-Resistant Melanoma Cells

Abstract: (1) BRAF mutations are associated with high mortality and are a substantial factor in therapeutic decisions. Therapies targeting BRAF-mutated tumors, such as vemurafenib (PLX), have significantly improved the overall survival of melanoma patients. However, patient relapse and low response rates remain challenging, even with contemporary therapeutic alternatives. Highly proliferative tumors often rely on glycolysis to sustain their aggressive phenotype. 3-bromopyruvate (3BP) is a promising glycolysis inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…In Figures S2 A‒S2D, our study found that GL-V9 had superior inhibitory effects on cell growth and glycolytic capacity compared to 3-bromopyruvate (3-BP), a potent HKII inhibitor. 72 , 73 The inhibitory effects of 3-BP are diminished by the increased expression of AKT, and the combination of GL-V9 and 3-BP resulted in much stronger apoptosis of PCa cells than either treatment alone ( Figures S2 E‒S2F).…”
Section: Discussionmentioning
confidence: 99%
“…In Figures S2 A‒S2D, our study found that GL-V9 had superior inhibitory effects on cell growth and glycolytic capacity compared to 3-bromopyruvate (3-BP), a potent HKII inhibitor. 72 , 73 The inhibitory effects of 3-BP are diminished by the increased expression of AKT, and the combination of GL-V9 and 3-BP resulted in much stronger apoptosis of PCa cells than either treatment alone ( Figures S2 E‒S2F).…”
Section: Discussionmentioning
confidence: 99%